Gene expression and functional abnormalities in XX/Sry Leydig cells - Yanai, Shogo; Baba, Takashi; Inui, Kai; Miyabayashi, Kanako; Han, Soyun; Inoue, Miki; Takahashi, Fumiya; Kanai, Yoshiakira; Ohkawa, Yasuyuki; Choi, Man Ho; Morohashi, Ken-ichirou (Nature Publishing Group, 2021)
The SRY gene induces testis development even in XX individuals. However, XX/Sry testes fail to produce mature sperm, due to the absence of Y chromosome carrying genes essential for spermatogenesis. XX/Sry Sertoli cells show abnormalities in the production of lactate and cholesterol required for germ cell development. Leydig cells are essential for male functions through testosterone production. However, whether XX/Sry adult Leydig cells (XX/Sry ALCs) function normally remains unclear. In this study, the transcriptomes from XY and XX/Sry ALCs demonstrated that immediate early and cholesterogenic gene expressions differed between these cells. Interestingly, cholesterogenic genes were upregulated in XX/Sry ALCs, although downregulated in XX/Sry Sertoli cells. Among the steroidogenic enzymes, CYP17A1 mediates steroid 17 alpha-hydroxylation and 17,20-lyase reaction, necessary for testosterone production. In XX/Sry ALCs, the latter reaction was selectively decreased. The defects in XX/Sry ALCs, together with those in the germ and Sertoli cells, might explain the infertility of XX/Sry testes.